CROWDED ROOM. Issue 3 (10th September 2013) - Dushnitsky, Gary
Abstract : Gary Dushnitsky's latest research seeks to uncover the reality behind the much talked about emergence of crowdfunding as a means of funding everything from the Statue of Liberty to rock albums.